THE ANALYSIS OF DERIVATION IN CONVERSATION SCRIPTS - atikah wati (Universitas Wiralodra, 2018)
Word derivation make the conversation more simple and specific to the topic. The case is many students didn’t recognise and aware of using it. this paper is trying to reveal the words derivation that the students use in their speaking class conversation whether or not it affected to the semantic. Dealing with vocabulary and grammar, speakers often choose certain vocabulary to express something and forming it into the correct grammatical rules, the choice of vocabulary that the speaker use during the planned speaking activity in the classroom and how this words implemented with the correct grammar in the form of literature dealing with morphology and semantic are the main focus of this paper. Many students didn’t really aware with the use of derivational words, 3 numbers of students conversational scripts didn’t insert any derivational words at all. While the other 2 insert very little derivational words. The method of analysis that the writer use to reveal the processes of derivation in more detail by noting three simultaneous processes, namely: a morphological process (e.g. changing the shape of an existing word by adding a prefix or suffix morpheme to an existing root morpheme) a syntactic process (changing the part of speech of a word, e.g. from verb to noun) and a semantic process (producing a new sense, agent, act, property).